Cell Energy Metabolism and Hyaluronan Synthesis. (January 2021) - Caon, Ilaria; Parnigoni, Arianna; Viola, Manuela; Karousou, Evgenia; Passi, Alberto; Vigetti, Davide
Hyaluronan (HA) is a linear glycosaminoglycan (GAG) of extracellular matrix (ECM) synthesized by three hyaluronan synthases (HASes) at the plasma membrane using uridine diphosphate (UDP)-glucuronic acid (UDP-GlcUA) and UDP- N- acetylglucosamine (UDP-GlcNAc) as substrates. The production of HA is mainly regulated by hyaluronan synthase 2 (HAS2), that can be controlled at different levels, from epigenetics to transcriptional and post-translational modifications. HA biosynthesis is an energy-consuming process and, along with HA catabolism, is strongly connected to the maintenance of metabolic homeostasis. The cytoplasmic pool of UDP-sugars is critical for HA synthesis. UDP-GlcNAc is an important nutrient sensor and serves as donor substrate for the O -GlcNAcylation of many cytosolic proteins, including HAS2. This post-translational modification stabilizes HAS2 in the membrane and increases HA production. Conversely, HAS2 can be phosphorylated by AMP activated protein kinase (AMPK), a master metabolic regulator activated by low ATP/AMP ratios, which inhibits HA secretion. Similarly, HAS2 expression and the deposition of HA within the pericellular coat are inhibited by sirtuin 1 (SIRT1), another important energetic sensor, confirming the tight connection between nutrients availability and HA metabolism.